Hourly Time Series of Air Emissions from Eastern Australia Power Plants, 2010-2019 - Garg, Maheshinderjeet (PANGAEA, 2020)
This dataset consists of air emissions from Eastern Australia power plants covering New South Wales, Victoria, Queensland, South Australia and Tasmania regions. The emissions have been estimated using 5-minute electricity generation time-series provided by National Energy Market (NEM). The hourly emissions are estimated from 2010 to 2019 for sulfur dioxide, nitrogen oxides, particulate matter (PM) split into PM10 and PM2.5 and mercury (Hg). The emission factors are developed using plant-specific details, official national statistics and scientific research.
Keywords: Air emissions; Australia; Power Plants